The Influence of Conflict of Interest and Organizational Culture on External Auditor Audit Quality - Fransiska; Martdian Ratna Sari (Asia Pacific Fraud Journal, 2025)
External auditors play a crucial role in ensuring the reliability of financial statements by accumulating and evaluating evidence and providing an independent opinion. However, audit quality can be affected by conflicts of interest and organizational culture. This study examines the impact of conflicts of interest and organizational culture on audit quality, drawing on role theory and attribution theory. Data were collected through questionnaires distributed to external auditors in the Jakarta area, resulting in a total of 46 respondents. SmartPLS 4 was used for the analysis. The analysis results indicate that conflicts of interest and organizational culture affect audit quality. These findings underscore the importance of managing conflicts of interest and fostering a strong organizational culture to enhance audit quality. This study contributes to the accounting literature by providing empirical evidence on the significance of these factors in ensuring high-quality and independent audit practices